Development and pilot study of family-centered neonatal palliative care - Na Zhang; Yong Chen; Lihui Zhu; Muhua Chen; Yuee Xiong; Tingwei Luo (Frontiers in Medicine, 2026)
Background The high global neonatal mortality rate, the variety of causes of death, and the poor quality of neonatal survival at the end of life make the implementation of neonatal palliative care (NPC) urgent. Developed countries have developed guidance models and systems for NPC. In developing countries, NPC is still in its infancy, with insufficient practice experience. Therefore, there is an urgent need to develop practice-oriented NPC models. Methods Based on the family-centered care (FCC) theory, this study adopted a combination of literature research, qualitative research and the Delphi method to develop a family-centered NPC (FCC-NPC) model. Using a before-and-after control method, 10 cases of end-of-life children in the neonatal department of a children’s specialty hospital in Hunan Province were selected as study subjects to observe the feasibility of model implementation and family satisfaction. Results We conducted two rounds of expert correspondence. The recovery rates of the first and second questionnaires were 100%. The average authoritative coefficients were 0.858. The Kendall W values ranged from 0.302–0.503 ( p < 0 0.01). Six level I indicators, 22 level II indicators, and 66 level III indicators were developed for FCC-NPC. In the pilot study, eight cases were fully completed and two cases were partially completed, for a completion rate of 80.00%. Family satisfaction scores were significantly higher after the pilot study than before the pilot study ( p < 0.05). Conclusion The FCC-NPC developed in this study has good science and practicality, and may provide a reference for NPC clinical practice.